(untitled) (Olhares, 2015)
The article analyzes the pedagogical approach in order to understand about improvisation, spontaneity and the creative process of Keith Johnstone. It discusses how traditional learning from the past denied the importance of intuition relegating it to the world of magic and religion called “primitive”. It discourses about how formal education shrinks the talent and how to find ways to combat the effect caused.